2021
DOI: 10.1186/s12903-021-01795-7
|View full text |Cite
|
Sign up to set email alerts
|

A new comprehensive oral health literacy scale: development and psychometric evaluation

Abstract: Background It has been widely accepted that oral health status is related to oral health literacy. The need to measure oral health literacy has led to the development of measurement instruments. This study aimed to develop a comprehensive instrument for adults and to examine its reliability and validity in China. Methods A three-step design process was used. First, a literature review and expert panel discussion were used to draw up a 37-item pool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Apart from the scarcity of available educational interventions in Poland [ 1 ], a failure to adjust them to the targets’ health literacy might be the reason why recommendations are not adhered to closely enough. While several tools measuring general and oral health literacy have been developed [ 25 , 29 , 30 ], it might be useful to develop or adapt a Polish culture- and context-sensitive scale measuring parents’ oral health literacy so as to find out which of its dimensions represent the biggest challenge. We believe it is an important next step and a joint task for dental professionals, public health specialists, and health promoters and educators.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from the scarcity of available educational interventions in Poland [ 1 ], a failure to adjust them to the targets’ health literacy might be the reason why recommendations are not adhered to closely enough. While several tools measuring general and oral health literacy have been developed [ 25 , 29 , 30 ], it might be useful to develop or adapt a Polish culture- and context-sensitive scale measuring parents’ oral health literacy so as to find out which of its dimensions represent the biggest challenge. We believe it is an important next step and a joint task for dental professionals, public health specialists, and health promoters and educators.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, low health literacy, defined as an inability to read, understand, and act on health information [ 24 ], is associated with poorer health outcomes and a lower use of prevention [ 25 , 26 , 27 , 28 ]. Oral health literacy (OHL) is an important component of health competence [ 29 ]. OHL may translate into oral health behaviours [ 30 ] and oral health status [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neck pain-specific Health Behavior in Office Workers (NHBOW) [141] Mental Health Literacy Scale for Healthcare Students (MHLS-HS) [153] The Comprehensive Oral Health Literacy (COHL) [154] Mental Health Literacy Scale for Depression Affecting the Help-Seeking Process [162] Mandarin Health Literacy Scale (MHLS) [169] eHealth Literacy Scale (eHLS-Web 3.0) [198] Frequently translated or validated (more than ten)…”
Section: Instrumentsmentioning
confidence: 99%
“…Moreover, due to the high prevalence of dental caries worldwide [ 18 ], there is increased interest in the relationships between oral health outcomes, literacy, knowledge, and behaviours [ 19 , 20 , 21 , 22 , 23 ]. It has been suggested that oral health knowledge and literacy (OHKL) strongly influence oral health status [ 24 ], particularly in paediatric populations [ 8 , 25 ], which is why these aspects need to be examined before any public health interventions are considered.…”
Section: Introductionmentioning
confidence: 99%